Effect of bow drawing technique on skilled archer postural stability: a case study - Kuch, A.; Debril, J.-F.; Domalain, M.; Tisserand, R.; Monnet, T. (Computer Methods in Biomechanics and Biomedical Engineering, 2020)
At the Olympic games, archers use a recurve bow to shoot arrows at a 122 centimeters diameter target set 70 meters away. Postural stability and consistency are therefore determinant in the archer`s performance.